Institute of Metals Division - Microscopic Observation of the Solidification of Cu-Ni Alloy Droplets - R. E. Cech; D. Turnbull (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1952)
THE supercooling behavior of pure liquid metal droplets has been described.' The solidification behavior of small droplets of Cu-Ni alloys as a function of composition is described herein. The Cu-Ni system is of interest for such an investigation because the components are miscible in all proportions in both the liquid and solid state and the phase diagram of the system, Fig. 1, is a type often encountered in metal systems. It was noted by Van Riemsdyk2 and others that the nature of the "blick" of gold droplets during assaying is not perceptibly affected by the content of the platinum group metals that are soluble in both liquid and solid gold. With the exception of these very qualitative observations there appear to have been no prior investigations of the supercooling of alloy droplets. A series of nine alloys varying in composition by 10 pct (nominal weight) steps was made using certified OFHC copper, 99.996 pct purity, obtained from the American Brass Co., and electrolytic nickel pellets, 99.92 pct purity, obtained from the International Nickel Co. The alloys were melted and cast in vacuo in a high frequency induction furnace. Segregation was minimized by chill casting into 1-in. diam steel molds. Each alloy rod was homogenized at a temperature 50°C lower than the solidus for 100 hr in dry hydrogen. Samples for solidification experiments and chemical analysis were machined from the same portion of each rod and at a depth of in. from the rod surface. A Car-boloy tool was used in taking turnings to minimize contamination of sample by the cutting tool. As a check, a number of samples for microscopic observation were chipped from the ingot with a fragment of pyrex glass. The resultant data in all cases agreed, within experimental error, with the data obtained from machined turnings. A number of small particles, 30 to 50 micron diam, of a Cu-Ni alloy were placed in a quartz vial 1/32 in. diam x % in. long. This was inserted into a platinum ribbon heater and mounted in a high temperature microscope stage. The general procedure followed in inserting samples into the stage and measuring the temperature of melting and solidification was the same as described in an earlier paper.' A chromel-alumel thermocouple was used to study alloys of 88.93 pct Cu, 80.62 pct Cu, and 72.27 pct Cu. A platinum-10 pct rhodium thermocouple was used for the remainder of the alloys. Procedure The assembled high temperature microscope stage was first evacuated and the sample given a 2 min in situ treatment at 900 °C in dry hydrogen to remove surface oxides which might otherwise catalyze crystal nucleation. After this treatment the atmosphere was changed to purified helium and melting and solidification were observed microscopically. It was not possible to determine the solidus with certainty. However, the liquidus temperature was measured very accurately since the surface of the particle changed in appearance from coarse and uneven to smooth, mirror-like within a few degrees. The visually determined liquidus temperature was checked by finding the highest temperature to which the particle could be heated such that it did not supercool upon lowering the temperature. This temperature which checked within experimental error with that found by observing surface change was assumed to be characteristic of the thermody-namic liquidus. In order to minimize the effect of selective evaporation of copper from the alloy, samples were changed frequently and the droplets were heated no more than 50 °C in excess of the liquidus temperature T,. When the latter conditions were fulfilled, T, values were reproducible. After melting, the temperature was decreased slowly until the particles solidified. The sudden release of heat of fusion on solidification caused the